Do Stock Options Overcome Managerial Risk Aversion? Evidence from Exercises of Executive Stock Options - Heron, Randall A.; Lie, Erik (Management Science, 2017)
We report that the probability that executives exercise options early decreases with the volatility of the underlying stock return. We interpret this to mean that executives’ subjective option value increases with volatility and that option grants increase executives’ risk appetite. Further decomposition reveals that the results are most pronounced for idiosyncratic volatility, consistent with our conjecture that executives believe they can better predict or influence the resolution of idiosyncratic uncertainty than systematic uncertainty and, thus, favor the former. Data are available at http://dx.doi.org/10.1287/mnsc.2016.2495 . This paper was accepted by Wei Jiang, finance.